The Effectiveness of Community Outreach in Increasing the Coverage of Community Based Management of Acute Malnutrition (CMAM) Program, in Rural Kassala Locality - Mohammed, Somiya Gutbi Salim; Mosmar, Zemzem Yebio Adam (Edelweiss Applied Science and Technology, 2018)
Community based Management of Acute Malnutrition (CMAM) is an innovative approach for managing acute malnutrition within the community. This study is a community based cross sectional study among communities covered by CMAM program in Rural Kassala locality, Kassala state, Sudan. The main objective was to evaluate the effectiveness of community outreach workers / volunteers in improving and increasing the coverage of the CMAM program. ENA SMART software was used to calculate the sample size of children under five, a total of (309) was subjected for MUAC and bilateral edema measurements to assess their nutritional status, and their households (200) were interviewed to obtain relevant data. All the community outreach workers / volunteers (62) were targeted by the study. The study revealed that, the prevalence of acute malnutrition (wasting) was 17.1%, and no significant difference in the prevalence of acute malnutrition between boys and girls (p=0.477). A point coverage calculation was used to estimate services coverage, the coverage of the program estimated by 64.2%. Also the result showed that 67.7% of the cases attending the feeding program were referred by the commu nity outreach workers / volunteers. The study concluded that the community outreach workers / volunteers doing an effective job, but needs more to strengthen their roles of identification and early detection cases